Defensive balance in elite football: Making reliable observations - Schulze, E.; Meyer, T. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: It has been found that teams show anti-phase coordination during goal-scoring opportunities in elite football (soccer; Moura et al., 2016). These contrasting movements can be interpreted as a perturbation of the defensive team`s balance in relation to the offensive one. The concept of defensive balance has been introduced before and deemed crucial for the efficacy of playing styles (Tenga et al., 2010). The aim of this study was to determine the reliability of expert observations of defensive balance to possibly extract patterns within successful attacking sequences. Methods: Ten performance analysts, coaches, and scouts (7±5yrs of experience with match analysis) analysed five clips involving goal-scoring opportunities in matches between different elite international teams in a randomised order. The defensive balance within the defending team was rated in 1s-intervals on a 5-point scale. A slope of every four consecutive logtransformed ratings was calculated to determine the time window where defensive balance was disturbed most strongly (SLP). After every clip, participants also had to indicate which second they deemed decisive during the attacking sequence (SEC). Agreement was calculated as the percentage of ratings corresponding to the mode, the most reported rating for one variable, and statistically tested with a paired samples T-test. Results: Ratings of defensive balance in 1s-intervals agreed by 58.2±3.8% between participants. The conversion of these ratings led to an agreement of 52.0±23.9% for SLP. A tendency towards a significantly higher agreement was found compared to SEC (36.0±11.4%; P=0.08). By including those ratings within 1s of the mode, the agreement of SLP and SEC increased to 70.0±14.1% and 50.0±18.7%, respectively. This allowance did not significantly change the agreement within methods (P=0.07&P=0.14), however the agreement within SLP was significantly higher than that within SEC after allowing for a 1s-variance (P=0.05). Discussion: The method that used the second-by-second ratings of defensive balance and transformed those into a slope describing the change in balance over a 4s-window (SLP), proved to be more reliable when allowing a 1s-deviation from the mode compared to a self-selected time frame (SEC). This shows that the concept of defensive balance requires more than merely subjective ratings of experts. The strong agreement within SLP could enable indicating what player actions are most detrimental to a team`s defensive balance. This might provide useful information towards improving team performance and the quality of opposition scouting.